Reflecting problems of administrative management of Steppe region in newspaper «Omskiy Vestnik» (1909–1917) - V. V Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the content of publications in the newspaper «Omsky Vestnik» devoted to activities of administrative institutions of the Steppe region. They contain information on personnel movements, information on the activities of various meetings and commissions, on the interaction of the regional administration and city government bodies. Mandatory decisions, orders and orders of the GovernorGeneral of the Steppe region and local governors were often published on the pages of the publication. Periodic printing is an important historical source, allowing to analyze the peculiarities of local government, to trace the problems that the administration of the region has been solving in certain years